HISTORY OF TASHKENT CITY POLICE SYSTEM (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article contains information about the general socio-political situation in the cities of Turkestan in the 19th century, as well as the order in the cities, the compliance of the established laws, rules and procedures by the population, who punishes those who do not comply and in what order, the service instructions of the law enforcement agencies. . Also, in the article, the new order system developed by the Turkestan General Governorate established in the lands occupied by the Russian Empire after the conquest of Central Asia has similarities and differences with the tasks and powers of the traditional order supervisors, scientific, practical, scientific-theoretical. studied in terms of in writing the article, the scientific developments of local and Russian researchers and historical sources and archival data of this period serve as the main source.